PERAN ORANG TUA DALAM PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 DI DESA SUKA DAMAI KECAMATAN RIMBO ULU, KABUPATEN TEBO - Anggia Ramadhani; Sri Rahayu; Wibi Wijaya (Labor Program Studi Pendidikan Sosiologi, 2023)
The role of parents is very important in improving children's learning outcomes during the learning period (online). The purpose of this research is to find out the role of parents in online learning during the Covid-19 pandemic in Suka Damai Village, Rimbo Ulu District, Tebo Regency. The method used in this study is a qualitative method. The results of the study show that parents are involved in children's learning, provide stimulus in the form of reward and punishment to children, pay attention to children's conditions, pay attention to children's learning difficulties, provide learning facilities for children, find it difficult to share time because of busy parents, signal or network constraints, and people's economy incapacitated old man